2021
DOI: 10.3390/foods10020200
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of 25 Essential Oils on the Stored Product Pest, Sitophilus granarius

Abstract: The granary weevil Sitophilus granarius is a stored product pest found worldwide. Environmental damages, human health issues and the emergence of resistance are driving scientists to seeks alternatives to synthetic insecticides for its control. With low mammal toxicity and low persistence, essential oils are more and more being considered a potential alternative. In this study, we compare the toxicity of 25 essential oils, representing a large array of chemical compositions, on adult granary weevils. Bioassays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…In developing countries, loss of cereal foods is considered the major problem due to pest infections through storage [5][6][7]. Many insects, mites, and fungi attack stored cereals and led to a decrease its quality in addition to losses from 9 to 20% [8].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, loss of cereal foods is considered the major problem due to pest infections through storage [5][6][7]. Many insects, mites, and fungi attack stored cereals and led to a decrease its quality in addition to losses from 9 to 20% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of M. spicata and V. negundo 5% showed maximum oral toxicity (90.00%) followed by O. sanctum and T. erecta leaf extract (86.67%) after 72 hr of treatment. Demetre et al (2021) reported that 5% essential oil of M. arvensis, O. sanctum and O. basilicum showed 100, 99.00 and 97.0% mortality of S. granarius, respectively after 24 hr of treatment (Table 1). Oil from V. negundo leaves showed high overall toxicity to the adults of S. zeamais (Liu et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The average (1.5μL/cm 3 ) concentration of M.spicata, M.piperita and M.pulegium oils caused 23.33%, 50.00% and 50% mortality against S. zeamais. Demeter et al (2021) reported that 5% of M.arvensis essential oils showed 100% mortality against S.granarius. and O. sanctum (99.00%) mortality against S.granarius at 24 hours after treatment and O.basilicum essential oils showed 97.70% mortality at 24 hours after treatment against S.granarius.…”
Section: Fumigant Toxicitymentioning
confidence: 99%